Environmental Policy and Renewable Energy in an Imperfectly Competitive Market - Alexander Haupt (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper analyses an electricity market in which a monopolist that employs fossil-fuel base-load and peak-load technologies competes against a fringe of renewable energy (RE) generators. The optimal technology and electricity mix can be decentralised by levying technology-dependent capacity taxes/subsidies in addition to technology-/state-dependent emission taxes. Whenever base-load capacity is taxed (subsidised), peak-load capacity is subsidised (taxed). A decline in RE capacity costs and an increase in the share of consumers on real-time prices predominantly raises emission taxes and brings them closer to their Pigouvian level, albeit with some qualifications. Capacity taxes/subsidies disappear when all consumers are on real-time prices and RE is about to fully crowd out conventional base-load capacity.
Keywords: Q42; Q48; Q58; H23; L13; 330; intermittent renewable energy; peak-load technology; base-load technology; emission tax; capacity tax/subsidy